2014
DOI: 10.1111/add.12636
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo‐controlled trial of bupropion in methamphetamine‐dependent participants with less than daily methamphetamine use

Abstract: Aims Two previous randomized trials found an effect for bupropion in reducing methamphetamine use in the subgroup with lower frequency of methamphetamine use at baseline. This study aimed to replicate these results by comparing bupropion versus placebo in methamphetamine dependent participants with less than daily methamphetamine use at baseline. Methods Methamphetamine dependent volunteers reporting methamphetamine use on ≤ 29 of past 30 days were randomized to bupropion 150mg twice daily (N=41) or placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 41 publications
1
40
1
Order By: Relevance
“…Several studies examining drug-use severity, for example, have identified frequency of use at treatment entry to be an important factor that affects treatment response (Simpson et al, 2002;Vaillant, 1988). Recent studies with clinical samples of MAdependent users also support the importance of considering MA-severity when examining posttreatment outcomes, since heavy or daily use is considered to increase one's risk for relapse (Brecht and Herbeck, 2014;Elkashef et al, 2008Elkashef et al, , 2012Heinzerling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examining drug-use severity, for example, have identified frequency of use at treatment entry to be an important factor that affects treatment response (Simpson et al, 2002;Vaillant, 1988). Recent studies with clinical samples of MAdependent users also support the importance of considering MA-severity when examining posttreatment outcomes, since heavy or daily use is considered to increase one's risk for relapse (Brecht and Herbeck, 2014;Elkashef et al, 2008Elkashef et al, , 2012Heinzerling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is considerable interest in identifying interventions that can help reduce relapse to MA use, particularly among subgroups of MA-dependent users. Medication studies, for example, have demonstrated that MA-dependent participants with lower baseline levels of MA use tend to have better outcomes (fewer MA-positive urine samples than those with higher baseline MA use (Elkashef et al, 2008;Heinzerling et al, 2014;Shoptaw et al, 2008). Similarly, in longitudinal outcome studies of MAdependent users (Brecht and Herbeck, 2014), lower MA severity at treatment admission serves as a strong predictor of posttreatment abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Bupropion has been shown to inhibit the amphetamine-and methamphetamine-induced release of DA in vitro (Gruner et al, 2009;Simmler et al, 2013b) and decrease methamphetamine self-administration in rats (Reichel et al, 2009) and monkeys (Schindler et al, 2011). Bupropion also reduced methamphetamine-induced subjective and cardiostimulant effects in humans (Newton et al, 2005(Newton et al, , 2006 and may reduce drug use in subsets of methamphetamine users (Elkashef et al, 2008;Heinzerling et al, 2014). These findings suggest a role for DA in both the rewarding and subjective effects of methamphetamine.…”
Section: Introductionmentioning
confidence: 91%
“…Thereby, the failure to provide at least two negative urine samples in the first three weekly tests would confer an enhanced risk of treatment failure (Brensilver, Heinzerling, Swanson, & Shoptaw, 2012). However, abstinence was significantly higher in those individuals with high medication adherence compared to those with low adherence in a patient population with low methamphetamine abuse (Heinzerling et al, 2014). Together, these findings suggest that a high degree of personalization and management is needed (Brensilver, Heinzerling, & Shoptaw, 2013).…”
Section: Bupropionmentioning
confidence: 99%